2015
DOI: 10.2118/174557-pa
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative Weathering of Diluted Bitumen Films

Abstract: Summary One of the issues for the pipeline transportation of diluted bitumen (dilbit) is the fate and behaviour of the dilbit if it is spilled in freshwater systems; in particular, the evaporation rate and the change in physical properties of the film after evaporation and exposure to water (weathering). In this study, the evaporative weathering of dilbit Cold Lake Winter Blend (CLWB) and light crude oil Alberta Sweet Blend (ASB) films were compared. Evaporation rates were measured for films on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The results indicated that the highest evaporated portion of CLWB was about 22% at 25 °C, which was lower than ASB (40%) under the same condition. Furthermore, the diluents could evaporate at all temperatures, while the heavier compounds started to evaporate when the temperature reached 60 °C (Yarranton et al, 2015). Similar results of evaporation rate were found by Environmental Canada (2013).…”
Section: Evaporationsupporting
confidence: 83%
See 4 more Smart Citations
“…The results indicated that the highest evaporated portion of CLWB was about 22% at 25 °C, which was lower than ASB (40%) under the same condition. Furthermore, the diluents could evaporate at all temperatures, while the heavier compounds started to evaporate when the temperature reached 60 °C (Yarranton et al, 2015). Similar results of evaporation rate were found by Environmental Canada (2013).…”
Section: Evaporationsupporting
confidence: 83%
“…Temperature has a profound impact on the evaporation rate of spilled oil (Environment Canada, 2013;Yarranton et al, 2015;Johannessen et al, 2020;Ortmann et al, 2020). Yarranton et al (2015) conducted several tests to investigate and compare the evaporation rate and the physical property changes of dilbit and light crudes in freshwater.…”
Section: Evaporationmentioning
confidence: 99%
See 3 more Smart Citations